Pengaruh Media Sosial, E-Lifestyle, dan Status Sosial Ekonomi Orang Tua Terhadap Perilaku Konsumtif Mahasiswa Ilmu Ekonomi Universitas Negeri Medan - Cici Kurnia Sari Lubis; Jesica Septi Leony Simanungkalit; Yeremi Siagian; Nasrullah Hidayat (CV. ULIL ALBAB CORP, 2024)
This research aims to determine the use of social media, E-Lifestyle and parents' socio-economic status on the consumption behavior of Economics students at Medan State University, both simultaneously and partially. The population in this research was Economics students from Medan State University, class of 2021, totaling 120 students with a research sample of 35 students. This study uses a quantitative approach. The results of this research obtained the regression equation Y = 0.167 + 0.143 MS + 0.274 EL + 0.502 SS. Social media, E-Lifestyle and parents' socio-economic status simultaneously influence the consumption behavior of Economics students at Medan State University with a contribution of 42.8%. Partially, social media influences consumptive behavior. E-Lifestyle influences consumptive behavior and parents' socio-economic status influences consumptive behavior.